Middle School Matters: Pioneering Photonics Education Using SparkAlpha Explore - Mahoney, Vanessa; Outler, Kristen; Vigneau, Robert; McComber, Kevin (Conference proceedings : Midwest Symposium on Circuits and Systems, 2024)
As a nation, it is imperative that we address the science, technology, engineering, and mathematics (STEM) skills gap and ensure that our future workforce is equipped to meet the needs of the global economy. As we continue to expand middle school career exploration, we are investing in the future of our students and also laying the foundation for a stronger, more resilient workforce. In 2022, President Biden signed the CHIPS and Science Act (CHIPS Act), allocating 52.7 billion to bolster American manufacturing, supply chains, and national security. The Act serves to broaden STEM opportunities for Americans, facilitating participation in cutting-edge industries, such as quantum computing and AI. It provides new opportunities to overlooked communities in STEM and secures U.S. manufacturing [1]. Spark Photonics Foundation launched its train-the-teacher model, SparkAlpha Explore, introducing today's youth to crucial STEM topics such as semiconductors, integrated photonics, and advanced manufacturing. This program sets the stage for future success for middle and high school students by engaging them with advanced STEM topics at a critical time in their studies.